2022
DOI: 10.1007/s12325-022-02360-6
|View full text |Cite|
|
Sign up to set email alerts
|

PRESTO 2: An International Survey to Evaluate Patients’ Injection Experiences with the Latest Devices/Formulations of Long-Acting Somatostatin Analog Therapies for Neuroendocrine Tumors or Acromegaly

Abstract: Introduction Real-world data evaluating patients’ injection experiences using the latest devices/formulations of the long-acting (LA) somatostatin analogs (SSAs) lanreotide Autogel/Depot (LAN; Somatuline®) and octreotide LA release (OCT; Sandostatin®) are limited. Methods PRESTO 2 was a 2020/2021 e-survey comparing injection experience of adults with neuroendocrine tumors (NETs) or acromegaly treated with LAN prefilled syringe versus OCT syringe for > 3 months in Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The safety profile is not different between OCT and LAN. However, from a practical point of view, LAN was reported to be easier to manage than OCT and less frequently complicated by pain and technical problems, because of the autogel formulation with a comfortable device and a fast administration [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The safety profile is not different between OCT and LAN. However, from a practical point of view, LAN was reported to be easier to manage than OCT and less frequently complicated by pain and technical problems, because of the autogel formulation with a comfortable device and a fast administration [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some participants indicated that their choice of HCP administration was influenced by the fear (14.1%) or the anxiety (11.1%) that could occur with independent injection, though out of all participants, only three reported that they felt "Very anxious" or "Extremely NETs or acromegaly treated with LAN or OCT, some degree of preinjection anxiety was reported by approximately half of the survey participants (LAN, 59.5%; OCT, 43.7%). 12 It is possible that enhanced training and support could increase patients' confidence in their own or their caregiver's injection abilities and, at least in part, help to mitigate preinjection anxiety and resistance to independent injections.…”
Section: Discussionmentioning
confidence: 99%
“…Of 119 patients who completed the questionnaire, only 2% of the 51 patients receiving LAN who answered the question, reported moderate to high anxiety prior to injection (vs. 11% of 66 patients treated with OCT) 11 . In the recent PRESTO 2 survey ( n = 304), which assessed the injection experience of patients with NETs or acromegaly treated with LAN or OCT, some degree of preinjection anxiety was reported by approximately half of the survey participants (LAN, 59.5%; OCT, 43.7%) 12 . It is possible that enhanced training and support could increase patients' confidence in their own or their caregiver's injection abilities and, at least in part, help to mitigate preinjection anxiety and resistance to independent injections.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' preference for at-home administration may be, in part, supported by having LAN as a ready-to-use pre-filled syringe. Indeed, patients have previously reported that they were less likely to experience prolonged pain or technical issues with this device than with the latest octreotide long-acting release formulation (Novartis) [12]. Additionally, in an international simulated-use study, nurses administering lanreotide strongly preferred the user experience of the LAN syringe used in this study (Somatuline Autogel) versus an alternative, the Lanreotide Pharmathen syringe [13].…”
Section: Discussionmentioning
confidence: 99%